ABNORMAL RETURNS, UNEXPECTED EARNING DAN RISIKO PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anam, A. Khoirul (Students Journal of Economic and Management, 2012)
This study aimed to determine the effect of the Unexpected Earnings and Abnormal Return whether the financial risks can be explanatory effect between Unexpected Earnings with Abnormal Return on banking companies listed on the Indonesia Stock Exchange. The dependent variable is the Cumulative Abnormal Return (CumAR) and the independent variable is the Standardized Unexpected Earnings (SUE), credit risk, interest rate risk, liquidity risk and solvency risk. This study population is banking companies listed in Indonesia Stock Exchange for the period 2006 to 2010 as many as 31 companies. The research sample includes 27 banking companies. The data used are secondary data from financial statements of banking companies in the study period. Samples were taken by using purposive sampling and sample selection criteria. The results showed that the Standardized Unexpected Earnings (SUE) effect on the Cumulative Abnormal Return (CumAR) and credit risk, interest rate risk and solvency risks affect the Cumulative Abnormal Return (Cumar) is proxied in Response Earning Coefisien (ERC). While liquidity risk is not proven to be the explanatory effect between Unexpected Earnings with Abnormal Return. Keywords: Cumulative Abnormal Return, Standardized Unexpected Earning, Earning Response Coefisien, risk.